FOREST FERTILIZATION WITH WOOD ASH AND AMMONIUM NITRATE IMPACT ON BIOGENIC ELEMEMENT MOVEMENT OF SOIL WATER - Muižnieks, Edgars; Matisovs, Ivars (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2019)
The work describes impact of the complex soil fertilization with ammonium nitrate and wood ash on the forest water in Myrtillosa mel. The paper provides information and results about chemical element migration in Myrtillosa mel soil and precipitation water.